Understanding Employee Turnover Patterns in Mexican Maquiladoras - Romero, Eric (2009)
Thousands of manufacturing jobs have left the United States for Mexico because of lower labor costs in relatively close proximity to the United States. Despite lower labor costs, high employee turnover can be a major problem for maquiladoras, particularly for firms focusing on quality and high value services and products. We used quantitative and qualitative data to explore turnover patterns and seek an explanation for the high turnover in maquiladoras. Analysis of exit data from 2,714 line workers over a 4-year period revealed two major yearly peaks in turnover. Additionally, results from interviews of current hourly wage personnel and management revealed several major causes of turnover. Overall, we provide an explanation for yearly patterns in turnover and other reasons for turnover that are not found in other papers about this issue. Methods are suggested to reduce turnover, and ideas for future research are discussed.